The malaria parasite chaperonin containing TCP-1 (CCT) complex: Data integration with other CCT proteomes - Wilkinson, Mark D.; Ferreira, Josie L.; Beeby, Morgan; Baum, Jake; Willison, Keith R. (Frontiers in Molecular Biosciences, 2022)
The multi-subunit chaperonin containing TCP-1 (CCT) is an essential molecular chaperone that functions in the folding of key cellular proteins. This paper reviews the interactome of the eukaryotic chaperonin CCT and its primary clients, the ubiquitous cytoskeletal proteins, actin and tubulin. CCT interacts with other nascent proteins, especially the WD40 propeller proteins, and also assists in the assembly of several protein complexes. A new proteomic dataset is presented for CCT purified from the human malarial parasite, Plasmodium falciparum (PfCCT). The CCT8 subunit gene was C-terminally FLAG-tagged using selection linked integration (SLI) and CCT complexes were extracted from infected human erythrocyte cultures synchronized for maximum expression levels of CCT at the trophozoite stage of the parasite’s asexual life cycle. We analyse the new PfCCT proteome and incorporate it into our existing model of the CCT system which is supported by the emergence of new data from biochemical and cell biological experiments in many eukaryotic species. Together with measurements of CCT mRNA and CCT protein subunit copy number and the post-translational and chemical modifications of the CCT subunits themselves, a cumulative picture is emerging of an essential molecular chaperone system sitting at the heart of eukaryotic cell growth control and cell cycle regulation.